Transcriptome changes associated with elongation of bovine conceptuses II: Differentially expressed transcripts in the endometrium on day 17 after insemination - P.M. Peixoto; J.J. Bromfield; E.S. Ribeiro; J.E.P. Santos; W.W. Thatcher; R.S. Bisinotto (Journal of Dairy Science, 2023)
ABSTRACT: The objective was to characterize endometrial transcriptome on d 17 of gestation in dairy cows according to conceptus length. Nonlactating Holstein cows (n = 48) were slaughtered 17 d after AI and the uterine horn ipsilateral to the corpus luteum (CL) was flushed with saline solution. Recovered conceptuses were classified as small (1.2–6.9 cm; n = 9), medium (10.5–16.0 cm; n = 9), or large (18.0–26.4 cm; n = 10). Samples of intercaruncular endometrium dissected from the caudal, intermediate, and cranial portions of the uterine horn ipsilateral to the pregnancy were pooled for analyses. Total mRNA was extracted from endometrial tissue and subjected to transcriptome analyses using the Affymetrix Gene Chip Bovine array. Data were normalized using the GCRMA method and analyzed by robust regression using the Linear Models for Microarray library within Bioconductor in R. Transcripts with P ≤ 0.05 after adjustment for false discovery rate and fold change ≥1.5 were considered differentially expressed. Functional analyses were conducted using the Ingenuity Pathway Analysis platform. Comparisons between endometria of cows carrying large versus small (LvsS), large versus medium (LvsM), and medium versus small (MvsS) conceptuses yielded a total of 235, 21, and 94 differentially expressed transcripts, respectively. Top canonical pathways included the antigen presentation pathway and Th1/Th2 activation pathways, both for LvsS and MvsS. Interferon-α and -γ were identified as activated upstream regulators, primarily based on differently expressed transcripts such as IDO1, ISG20, WARS, LGALS9, IFI44, and PSMB9 (LvsS and MvsS). For LvsS, regulator analyses revealed predicted activation of FOXO1, IFN, NFACTC2, IL-12, IL-6, and IL-18, whereas it depicted inhibition of IL10RA and ZBTB1. Changes in these regulators were associated with a downstream activation of leukocytes, as well as quantity and expansion of T lymphocytes. Canonical pathways associated with the comparison LvsM included cell cycle G2/M DNA damage checkpoint regulation, cell cycle control of chromosomal replication. Moreover, tretinoin was predicted, as activated in upstream analysis for the same comparison. In conclusion, most of the differently expressed transcripts in the endometrium on d 17 of gestation were identified between cows carrying small conceptuses compared with counterparts carrying medium and large conceptuses and were involved with pathways associated with modulation of the immune response.